AUTHENTIC HAPPINESS REMAJA PEREMPUAN DARI KELUARGA BROKEN HOME DALAM HUBUNGAN ROMANTIS - Triyono, Triyono; Ayuningrum, Tri (Jurnal Psikohumanika, 2024)
The happiness of having a romantic relationship is the dream of every woman from a broken home. However, romantic relationships for women from broken homes do not always go well. Therefore, this research aims to describe the authentic happiness of female adolescents who are victims of broken homes in romantic relationships in Kartasura District, Sukoharjo Regency. This study uses a phenomenological qualitative method. The informants of this study were four young female informants from broken home families who were selected using a purposive sampling technique. Data collection techniques in this study were semi-structured interviews, participant observation, and documentation through research informant social media. The credibility of the data using the method triangulation technique. The data analysis uses the Interpretative Phenomenological Analysis (IPA) technique. The results of the study show that the authentic happiness of young women from broken home families who have romantic relationships is formed by their ability to rise from adversity in family conditions, positive meaning of life, desire to improve the future, and supportive social support from family, friends, and lovers. . External factors that affect the authentic happiness of young women from broken home families are religiosity and education. For young women from broken homes, having a romantic relationship can minimize psychological problems due to family dysfunction. On the other hand, romantic relationships among young women from broken home families encounter several obstacles that are prone to lead to toxic relationships.